GOLD AND MERCURY IN THE PROCESSES OF ORE FORMATION IN KAMCHATKA - V. A. STEPANOV (Известия высших учебных заведений: Геология и разведка)
The main features of the difference and similarity of the physical and chemical properties of gold and mercury have been given, which  determine their behavior in the natural processes of formation of  deposits of both metals in Kamchatka. It has been shown that the  difference in the properties of gold and mercury led to the  emergence of independent monometallic deposits, differing in  connection with intrusive formations, in depth and temperature of  ore formation. The similarity of the properties of these elements  determined the appearance of mercury minerals on gold ore deposits and gold in mercury deposits, as well as the formation of complex  gold-mercury deposits. Four geological-industrial types of gold- mercury deposits have been distinguished: the Knoxville, the Carlin,  the Kyuchus and the Chemlian ones, which include deposits with  large gold reserves both abroad and in Russia. The identification of  gold deposits, including through the revision of mercury ore  occurrences and deposits of Kamchatka for gold presence, will strengthen the mineral resources base of gold in this region.